2008
DOI: 10.1128/jcm.02486-07
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Trichomonas vaginalis DNA in Urine Specimens

Abstract: Trichomonas vaginalis is an important pathogen in both men and women. Culture is considered the diagnostic gold standard, although studies have shown that PCR is more sensitive than either culture or wet mount for the diagnosis of T. vaginalis infections. We sought to identify a simple method for stabilizing T. vaginalis DNA in urine samples that could be easily applied to molecular testing. The stability of T. vaginalis DNA in 40 urine samples was assessed by storage for various times at either 4°C or room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Cannas et al (2009) discovered that only study location and the addition of EDTA correlated with urinary DNA stability. EDTA preservatives for urine are commonly prepared to a final concentration of 10 mM using commercially available urine transport tubes sold specifically for downstream molecular analysis (Ingersoll et al, 2008). Milde et al (1999) found that storing urine at room temperature with sodium azide for 30 days or at -20°C with EDTA for 72 days provided the best protocol for the analysis of human DNA.…”
Section: Populationsmentioning
confidence: 99%
“…Cannas et al (2009) discovered that only study location and the addition of EDTA correlated with urinary DNA stability. EDTA preservatives for urine are commonly prepared to a final concentration of 10 mM using commercially available urine transport tubes sold specifically for downstream molecular analysis (Ingersoll et al, 2008). Milde et al (1999) found that storing urine at room temperature with sodium azide for 30 days or at -20°C with EDTA for 72 days provided the best protocol for the analysis of human DNA.…”
Section: Populationsmentioning
confidence: 99%
“…Ingersoll et al recently suggested that the stability of T. vaginalis DNA in urine could be improved with the use of a urine preservative transport kit. This method, while useful only for molecular diagnosis, could serve to substantially improve the sensitivity of molecular testing (36). PCR for the diagnosis of T. vaginalis is also available, but unlike for infections such as gonorrhea and chlamydia, in which PCR appears to have greater sensitivity than culture methods, PCR for trichomoniasis in women does not appear to offer a diagnostic advantage.…”
Section: Diagnosis Of T Vaginalismentioning
confidence: 99%
“…However, studies on other pathogens in different clinical specimens have shown a negative effect on molecular testing when kept at ambient temperature for extended periods of time (Hasan et al, 2012, Ingersoll et al, 2008. In that context, the manufacturer of the Xpert assay recommends that sputum samples be kept for no longer than 3 days at ambient temperatures up to 35° C until processing (Banada, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%